Geophysical characterization methods for sweet spots in shale oil: A case study of Niuzhuang Subsag in Shengli Oilfield - ZHANG Qiang; WANG Jing; ZHOU Haiting; LÜ Shichao (Youqi dizhi yu caishoulu)
In view of the insufficient applicability of geophysical characterization methods for sweet spots in shale oil in Niuzhuang Subsag， the core and logging data were used to analyze the physical characteristics of different types of lithofacies based on basic research， and the combinatorial lithofacies models were established for AVO forward analysis， so as to determine the elastic parameters of different lithofacies combinations. The intersection analysis was conducted using the elastic parameters obtained from prestack inversion to explore the spatial distribution of dominant lithofacies combinations. The shale oil and gas resources are rich in the terrestrial rifted lake basin in Jiyang Depression， with developed fractures and great potential for exploration and development. The favorable aspects of fractures for shale oil development are that they can effectively increase the production capacity of shale oil reservoirs， while the unfavorable aspects are that they increase the difficulty of drilling and cause frequent well kicks and lost circulation during drilling， which seriously affects the efficiency of drilling. Therefore， the accurate prediction of fractures has been a major problem in the exploration and development of shale oil in this block. In this paper， the anisotropy of the reflection coefficient of P-wave was theoretically analyzed. Based on the development characteristics and distribution pattern of shale oil fractures in the study area， OVT domain data were used to analyze the sub-azimuth stack and seismic attribute difference， and AVAZ inversion of pre-stack OVT domain seismic data was performed based on P-wave amplitude azimuthal anisotropy fracture prediction technique， so as to predict the fracture azimuth and development strength. The fracture results predicted by the pre-stack anisotropy inversion prediction were compared with actual drilling conditions and imaging logging results， and they were highly reliable， providing effective technical support for subsequent shale oil exploration and development. According to the relationship between the in-situ stress of shale oil reservoirs and the curvature attributes and elastic parameters， Young’s modulus， Poisson’s ratio， and other parameters obtained from pre-stack inversion were combined with the curvature attributes to predict the magnitude and direction of horizontal in-situ stress. Through the above research， the petrophysical and geophysical response characteristics of the sweet spots in Niuzhuang Subsag were clarified， and the geophysical characterization methods for sweet spots were established. These methods were used to comprehensively characterize the favorable target areas of shale oil.